N. Chabani Manganyi, Apartheid and the Making of a Black Psychologist: A Memoir (Historia, 2021)
N. Chabani Manganyi is the first qualified black clinical psychologist in South Africa. Heis a biographer, a writer and a theorist who has intensively written on the subjectiveexperiences of black people. In Apartheid and the Making of a Black Psychologist,Manganyi turns to himself as the subject of study by utilising an autobiographicalmethod. This method is plausible, as it is empowering. In what Manganyi calls “the storyof how I became a man, a citizen and a scholar” (p. xi), he offers a narrative of a blackman negotiating his identity during apartheid in South Africa. This act of revealing one’s experience using their own voice is empowering, to both the writer and the reader.Manganyi’s story is therefore a reassuring one, it is a story of resilience and triumph.In writing this review, it is important that I position myself as a young, black woman,psychologist born post 1990. The familiarity of this story to mine is of personal interest.Although I can never fully align the experiences expressed by Manganyi in his memoirto those of today’s young psychologists, it is still important to note that there remaintraces of Manganyi’s isolated and racialised experience in many of us. My personalexperiences with the psychology curriculum as a student are evidence to this. Inengaging with this book and many other works of Manganyi, I wonder how my ownstory and experiences of navigating academia and studying psychology would havebeen different had I been introduced to Manganyi’s writing earlier, perhaps in apsychology class.
Keywords: N. Chabani Manganyi; Apartheid; Black Psychologist; South Africa; black communities